2023
DOI: 10.3390/w15152711
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Saturated Hydraulic Conductivity (Ksat) Estimations from Pedotransfer Functions (PTFs) and Field Observations in Riparian Seasonal Wetlands

Abstract: Accurate saturated hydraulic conductivity (Ksat) predictions are critical for precise water flow estimations. Pedotransfer functions (PTFs) have been used to estimate Ksat based on soil structural and textural properties. However, PTF accuracy must be validated with observed Ksat values to improve confidence in model predictions. A study was conducted in the seasonal wetlands of a representative mixed land-use watershed in West Virginia (WV), USA. The observed data included soil characteristics and observed pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…The field Ksat data collection did not include subsurface soil Ksat values. Ksat may vary with soil depth, and this omission could potentially affect model predictions, as more observed data might enhance the model performance and reduce model simulation uncertainty [20,25,31,69,79]. In addition, this study showed that 1 m DEM could provide a more detailed and accurate analysis in this study relative to coarser DEMs.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 81%
See 1 more Smart Citation
“…The field Ksat data collection did not include subsurface soil Ksat values. Ksat may vary with soil depth, and this omission could potentially affect model predictions, as more observed data might enhance the model performance and reduce model simulation uncertainty [20,25,31,69,79]. In addition, this study showed that 1 m DEM could provide a more detailed and accurate analysis in this study relative to coarser DEMs.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 81%
“…Furthermore, Ksat is highly spatially variable and is greatly influenced by soil texture, compaction, and other factors [8][9][10]. There are many different techniques to directly determine Ksat in the field and laboratory (e.g., pumping, permeameter tests, and slug tests), as well as indirect methods: pedotransfer functions (PTFs), artificial neural networks (ANNs), support vector machine (SVM) models, and hydrological modeling [6,9,[11][12][13][14][15][16][17][18][19][20]. All methods of estimating Ksat often provide varying results due to differences in measurement and calculation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in seasonally flooded palustrine emergent riparian wetlands of a second-order reach in the West Run Watershed (WRW) located in northeastern Morgantown, West Virginia (WV), USA (Figure 1). The study reach drains into the third-order West Run Creek, a Monongahela River tributary [31]. The soil texture of the study reach was predominantly sandy, and the observed average saturated hydraulic conductivity (Ksat) ranged from 35.90 to 169.64 m/d [31].…”
Section: Site Descriptionsmentioning
confidence: 99%
“…The study reach drains into the third-order West Run Creek, a Monongahela River tributary [31]. The soil texture of the study reach was predominantly sandy, and the observed average saturated hydraulic conductivity (Ksat) ranged from 35.90 to 169.64 m/d [31]. The soil's average dry bulk density, porosity, and degree of saturation were 1.27 g/cm 3 , 0.57, and 0.94, respectively [31].…”
Section: Site Descriptionsmentioning
confidence: 99%
“…A previous study by Phaneuf et al, (1999) reported that, irrespective of land practices, a large portion of water flow is transported by a small portion of the soil volume, demonstrating that the spatial hydraulic characteristics of soils are highly variable. The K sat measurements should therefore be evaluated carefully to ensure that the values obtained are accurate and appropriate for the intended use (Abesh and Hubbart 2023).…”
Section: Introductionmentioning
confidence: 99%